Strategic negotiations: three essentials for successful partnerships with startups. Issue 1 (21st January 2019) - Freytag, Rudolf
Abstract : Purpose: The author presents a tried-and-tested strategy for how startups can systematically and efficiently negotiate partnerships with established companies. Design/methodology/approach: The concept consists of three elements: strategic balance, stakeholder alignment, and negotiation space. Real-world examples illustrate how this strategy can be applied. Findings: The "strategic balance" element weighs the strategic benefits of the partnership against the strategic costs. This determines the negotiation strategy. The "stakeholder alignment" element gives due consideration to the interests and priorities of all stakeholder groups. Lastly, the "negotiation space" element is instrumental in streamlining the negotiations by focusing on the issues that are actually negotiable. Practical implications: The concept can generally be applied to all aspects of negotiations between startups and established companies and has a long and proven track record in the real world. The issue of strategic balance in particular is useful in recognizing the strategic costs, which are sometimes hard to discern and only manifest themselves down the road, and comparing them with the strategic benefits, which are frequently obvious. A careful stakeholder alignment increases the chance that negotiations will succeed while building a foundation for constructive collaboration in the eventual partnership. Originality/value: Startups that use this tried-and-tested strategy have a tool that can help them systematically and efficiently negotiate partnerships with established companies. The tool also helps the partners recognize early on whether negotiations actually have any prospect for success. The concept can also serve as a guideline for a corporate in negotiating a successful partnership with a startup.